Cognitive Impairment and Cardiovascular Disease: A Comparison of Risk Factors, Disability, Quality of Life, and Access to Health Care. (January 2020) - Adams, Mary L.; Grandpre, Joseph; Katz, David L.; Shenson, Douglas
Objectives: Cognitive difficulties or impairment may be an early step in the development of dementia. Several modifiable risk factors for cardiovascular disease (CVD) may also increase the risk of dementia. The objective of our study was to compare adults with subjective cognitive impairment (SCI), using the Behavioral Risk Factor Surveillance System (BRFSS) cognitive disability measure, with adults who reported CVD. Methods: We examined data on 3 key outcomes among 302 008 adult respondents aged ≥45 in the 2017 BRFSS: respondents with SCI only, respondents with CVD only, and respondents with both conditions. We compared measures of disability, quality of life, access to health care, and a composite measure of the following 7 risk factors: current smoking, diabetes, high cholesterol, hypertension, inadequate fruit and vegetable consumption, obesity, and sedentary lifestyle. We also estimated population-attributable risk (PAR). Results: Among respondents, 7.9% reported SCI only, 11.1% reported CVD only, and 3.2% reported both conditions, with differences by age and sex. Adults with SCI only were more likely than adults with CVD only to report other disability, worse access to health care, and poorer quality of life, even though adults with CVD were older. Compared with adults with neither condition, adults with any of the 3 outcomes were more likely to report having each of the 7 risk factors; we found a linear association with an increasing number of risk factors. Five or 6 risk factors contributed to PARs for each of the 3 key outcomes. PARs for SCI only were highest for ever smoking (17.2%) and sedentary lifestyle (12.8%), whereas for CVD only, PARs were highest for hypertension (35.5%) and high cholesterol (22.9%). Conclusion: Despite differences between adults with SCI and adults with CVD in several demographic and health-related measures, the overall similarity in PARs for SCI and CVD suggests potential benefits from using effective CVD interventions to address SCI.